2008
DOI: 10.3324/haematol.12206
|View full text |Cite
|
Sign up to set email alerts
|

Lower dose rituximab is active in adults patients with idiopathic thrombocytopenic purpura

Abstract: Rituximab 375 mg/m 2 weekly for four weeks has significant activity in patients with immune thrombocytopenia. We evaluated the activity of lower dose rituximab (100 mg iv weekly for 4 weeks) in 28 adults with idiopathic thrombocytopenic purpura. Overall (platelet count > 50ϫ10 9 /L) and complete responses (platelet count > 100ϫ10 9 /L) were achieved in 21/28 (75%) and 12/28 (43%) patients respectively. The median time to response and time to complete response were 31 and 44 days respectively. After a median fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 20 publications
6
62
2
5
Order By: Relevance
“…In one small series sustained complete response was achieved in four of 7 patients (57%) and no infusion reactions were seen [59]. In a slightly larger series overall and complete responses were achieved in 21/28 (75%) and 12/28 (43%) patients respectively [60]. Further studies are warranted to confirm these preliminary data, as a lower dose may be associated with a lower risk of toxicities.…”
Section: Rituximabsupporting
confidence: 55%
See 1 more Smart Citation
“…In one small series sustained complete response was achieved in four of 7 patients (57%) and no infusion reactions were seen [59]. In a slightly larger series overall and complete responses were achieved in 21/28 (75%) and 12/28 (43%) patients respectively [60]. Further studies are warranted to confirm these preliminary data, as a lower dose may be associated with a lower risk of toxicities.…”
Section: Rituximabsupporting
confidence: 55%
“…A low-dose rituximab regimen (100mg weekly for 4 consecutive weeks) has been explored in ITP patients, with encouraging results [59,60]. In one small series sustained complete response was achieved in four of 7 patients (57%) and no infusion reactions were seen [59].…”
Section: Rituximabmentioning
confidence: 99%
“…Additional mechanisms of action have been proposed, including the indirect modulation of T-cell homeostasis [7]. Three noncontrolled studies have reported the efficacy of RTX given at lower doses (100 mg every week for 4 weeks), and have shown good short-term response rates [8][9][10]. In rheumatoid arthritis (RA), RTX has been licensed at a fixed dose (1,000 mg on days 1 and 2), though this arbitrary regimen was chosen by the manufacturer in both phase II and III trials [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effectiveness of low-dose RTX, possible mechanisms may involve the small amount of abnormally activated B-lymphocytes in TTP, as opposed to clonal B-lymphocytes in malignant lymphoma; thus, a lower RTX dose may eliminate the abnormally activated B-lymphocytes. In addition, certain studies have demonstrated that after the first week of RTX treatment, peripheral blood CD20 + cells had almost disappeared in ITP patients (15,16). Therefore, for autoimmune diseases, the current authors hypothesized that RTX may not require a dose as large as that used in B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%